Find the remainder when
1 ≤ i < j ≤ 1 0 0 ∏ ( i 2 + i j + j 2 )
is divided by 1 0 1 .
Note: i , j range over all positive integers between 1 and 1 0 0 (inclusive) satisfying i < j .
Details and assumptions
- You might use the fact that
1
0
1
is a prime.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I have reason to believe that the answer is actually 1 0 0 . This has been checked with Mathematica and Prelude. I will try and expand on this as there might be a flaw in your argument.
EDIT: OK. Here we have a claim saying that the answer is indeed 1 0 0 as it is actually − 1 because of a sgn function on the swapping of the product to cube terms was omitted. The permutation x → x 3 has sign − 1 therefore the answer is 1 0 0 .
EDIT 2: Might I add that this is in no means an attack on the solution. I respect your work and I am pointing out this possible flaw with all due respect.
Log in to reply
Yes, I forgot to check the signs. I do believe that it should be 100.
@Sreejato Bhattacharya Do you agree that the answer should be 100?
Log in to reply
Yes, so sorry for that. I have changed the problem statement.
Log in to reply
@Sreejato Bhattacharya – I think it's better to stick to the original intention of the problem (and it's simplicity). I've updated the answer to 100.
@Sreejato Bhattacharya – The sign is sneaky so don't worry! I enjoyed your problem thoroughly!
Log in to reply
@A Former Brilliant Member – not fair, i proccedeed exactly as Calvin but i wrote -1 instead of 100 >:(
Problem Loading...
Note Loading...
Set Loading...
I enjoyed this question. Here is my solution.
Notice that ( i 2 + i j + j 2 ) = i − j i 3 − j 3 . This strongly suggests that we should look at ∏ ( i − j ) and ∏ ( i 3 − j 3 ) .
Claim: { i 3 ( m o d 1 0 1 ) } ≡ { i ( m o d 1 0 1 ) } .
Proof: As hinted by Sreejato, we will use the fact that 1 0 1 ≡ 2 ( m o d 3 ) .
Suppose we have a 3 ≡ b 3 ( m o d 1 0 1 ) . By Fermat's Little Theorem, since 101 is prime, we know that a 1 0 0 ≡ b 1 0 0 . Hence, we conclude that
a ≡ a × ( a 3 3 ) 3 = a 1 0 0 ≡ b 1 0 0 ≡ b ( m o d 1 0 0 ) . □
This shows that the map of i → i 3 ( m o d 1 0 1 ) is one-to-one. Since they have the same cardinality, thus they are the same set.
Claim: Let ρ ( i ) = i 3 denote the permutation on the (non-zero) cubic residues mod 101. Then, the order of ρ is odd.
Proof: Let ω be a primitive element of the non-zero residues mod 101. Then ρ ( ω k ) = ω 3 k and so we have the map ρ ∗ ( k ) = 3 k on Z 1 0 0 . By analyzing the orbits, we see that there are 11 cycles (with starting values of 0, 1, 2, 4, 5, 10, 11, 20, 25, 50, 55) hence, the order is 100-11 = odd. □
As such,
1 ≤ i ≤ j ≤ 1 0 0 ∏ ( i 3 − j 3 ) ( m o d 1 0 1 ) = 1 ≤ i ≤ j ≤ 1 0 0 ∏ ( ρ ( i ) − ρ ( j ) ) ( m o d 1 0 1 ) = s g n ( ρ ) × 1 ≤ i ≤ j ≤ 1 0 0 ∏ ( i − j ) = − 1 ≤ i ≤ j ≤ 1 0 0 ∏ ( i − j )
This allows us to conclude that
1 ≤ i ≤ j ≤ 1 0 0 ∏ ( i 2 + i j + j 2 ) ≡ − 1 ≡ 1 0 0 ( m o d 1 0 1 ) .